Fracture of a Femoral Revision Stem following a Technical Failure - Falko Herold; Henk Eijer (Case Reports in Orthopedics)
We report about a fracture of a modular, uncemented femoral revision stem (Zimmer, Revitan®) due to a not previously described intraoperative technical problem. During implantation, a small ring, part of the proximal part of the trial stem, was left on the distal part of the definite stem. Following this, the top screwcap of the proximal part of the definite stem could not be tightened properly. However, the stem was thought to be stable, and the situation left. Two and a half years later, the proximal part of the stem fractured and the situation became unstable. It is very useful to know about this ring and that it should always be removed, otherwise, there is possibility that it may be left on the definite distal part of the stem with the possibility of a later fracture.